1975
DOI: 10.1001/archneur.1975.00490460035002
|View full text |Cite
|
Sign up to set email alerts
|

Nervous System Degeneration Produced by the Industrial Solvent Methyl n-Butyl Ketone

Abstract: Because of a number of cases of peripheral neuropathy that occurred in factory workers employed in a fabric-printing plant in 1973, chronic inhalation experiments have been conducted using the printing-ink solvents methyl n-butyl ketone (MBK) and methyl iso-butyl ketone (MIBK). After four months of intermittent respiratory exposure to 1,300 parts per million (ppm) MBK, all six rats tested developed severe symmetric weakness in the hindlimbs. Morphological studies showed massive focal axonal enlargements contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0
1

Year Published

1976
1976
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(21 citation statements)
references
References 11 publications
1
19
0
1
Order By: Relevance
“…The observation that the vestibulocerebellar sway is affected by n-hexane is compatible with the data in rats that histopathological changes (distal axonal swelling and degeneration) were caused by n-hexane in the vermis 36,37) , which contains the vestibulocerebellum (lower vermis). Similarly, the observation of the increase in the less than the estimated level in the present study-i.e.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The observation that the vestibulocerebellar sway is affected by n-hexane is compatible with the data in rats that histopathological changes (distal axonal swelling and degeneration) were caused by n-hexane in the vermis 36,37) , which contains the vestibulocerebellum (lower vermis). Similarly, the observation of the increase in the less than the estimated level in the present study-i.e.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, our study suggested that the possibility that xylene can inhibit the effect of n-hexane on postural balance, i.e. the vestibulocerebellar type of sway was inversely related to MHA, denying adverse effect xylene, which has been known as a neurotoxic substance 37,[45][46][47] . This coincides with the observation that n-hexane-induced slowing of peripheral 31,36,37) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peripheral neuropathy has recently been studied extensively in typical work environments (1,5,7,14), in "sniffers" (8,17,18,23), and in experimental animals (21,27,29,30). In such studies the causes of neuropathy have been n-hexane (14,27,33), trichloroethylene (7), and methyl butyl ketone (1,21,29,31). For "sniffers" the etiologic agents have often been referred to only as "volatile hydrocarbons" (22,32).…”
mentioning
confidence: 99%
“…In the case of 2-hexanone, there is very robust toxicity information particularly as it relates to neurotoxicity. Subchronic inhalation exposure to 2-hexanone at concentrations ranging from 200 ppm to 1600 ppm is associated with the observance of peripheral neuropathy in chickens, rats, cats, and monkeys (Abou-Donia et al 1985;Mendell et al 1974;Spencer et al 1975;Duckett et al 1974). Johnson et al (1979) reported that rats and monkeys that inhaled 100 ppm of 2-hexanone for 9 months developed abnormal neurophysiologic indicators, and this exposure was equivalent to a daily 8-hour TWA of 75 ppm.…”
Section: Toxicology Summary and Data Analysismentioning
confidence: 99%